Clarification of fire characteristics in a road tunnel based on numerical and laboratory studies - Lanchava, Omar (Edelweiss Applied Science and Technology, 2024)
Critical velocity for longitudinal ventilation, as is accepted under the emergency ventilation strategy, is a decisive factor to prevent backlayering. The results of physical and thorough numerical modeling showed that the critical velocity in inclined tunnels in case of descending ventilation and of strong fires would no longer be an important indicator within the projects. Besides, the location of the fire has a significant impact on the thermal physics and aerodynamics of the ventilation flow and the surrounding mining massif. A natural consequence of this is significant variation in critical velocity and backlayering length, which greatly affects the planning and implementation of life-saving measures. The article presents scenarios of underground fire development and analysis of accompanying processes, performed using numerical modeling in the FDS environment. The variation of the critical velocity of longitudinal ventilation, the length of the reverse flow of combustion products and the gradient-factor depending on the fire power, tunnel geometry and other variabilities is shown. It is noted that the critical value of the Froude number, like the critical ventilation rate, are not constant values in complex processes occurring underground. Specific numerical examples show that thermally and mechanically conditioned ventilation flows are algebraically summed, and without considering these circumstances, the processes of rescuing people from underground fires will certainly become more complicated. The paper found, both theoretically and through numerical modeling, that severe fires in tunnels can cause dynamic pressures greater than the static pressure of the fans. The observed dynamic pressures can reverse downward ventilation flows in tunnels with slopes of 3% or more. This work puts on the agenda not only a thorough detailed description and analysis of fire cases, but also the need to develop a clear algorithm of actions taking into consideration the geometry, location, natural conditions and ventilation systems of a specific tunnel, taking into consideration also the scenario of the expected fire. The results obtained should be communicated to rescuers and tunnel service workers through theoretical studies and training. The proposed paper is socially oriented, aimed at improving emergency ventilation technology and thus increasing safety in case of fires in road tunnels, which is an important socio-political and public task.